Investigating the effect of humility of Muslim leaders on the moral behaviours of followers and spirituality at work in Islamic society - Boudlaie, Hasan; Boghosian, Albert; Chandra, Teddy; Ibraheem Shelash Al-Hawary, Sulieman; Abed Hussein, Rasha; Ghazi Talib, Saad; Mutlak, Dhameer A.; Muda, Iskandar; Iswanto, A. Heri (Hervormde teologiese studies, 2022)
Organisations are increasingly involved in what they call ‘ethical dilemmas’, that is, the conditions under which wrongdoing and righteous deeds must be defined once again because the line between right and wrong has blurred more than ever. In general, human beings have special moral characteristics in the individual and personality dimension that shape their thoughts, speech and behaviour. It is possible that the same people in the same position and organisation could be affected differently, and their ideas, speech and behaviour affect the efficiency and effectiveness of the organisation. Ethics can have positive or negative consequences at each organisational level. One of the effective factors on the occurrence of employees’ ethical behaviours is the role of spirituality in the work environment and humility of leaders. The purpose of this study is to investigate the effect of humility of Muslim leaders on the moral behaviours of followers and spirituality at work in Islamic society. The statistical population of the study was 370 Muslim employees of International Islamic University Malaysia. After distributing the questionnaires among the statistical population, 352 questionnaires were returned. The validity of the questionnaires was confirmed by the content validity method, and its reliability was confirmed by Cronbach’s alpha. In this research, the structural equation modeling approach and Amos software were used to analyse the data. All hypotheses were confirmed at a 95% significance level. The results showed that the humility of leaders has a positive and significant effect on spirituality in the workplace and work ethic of followers. Spirituality in the workplace has also a positive effect on employees’ work ethic.Contribution: It is recommended that the officials of organisations should pay attention to spirituality in the workplace and the humility of managers and supervisors towards employees in order to promote work ethics. Further, it can be concluded that organisations can increase the ethical behaviours of employees by promoting the components of organisational spirituality.